Multimodality cardiac evaluation in children and young adults with multisystem inflammation associated with COVID-19. (7th August 2020) - Theocharis, Paraskevi; Wong, James; Pushparajah, Kuberan; Mathur, Sujeev K; Simpson, John M; Pascall, Emma; Cleary, Aoife; Stewart, Kirsty; Adhvaryu, Kaitav; Savis, Alex; Kabir, Saleha R; Uy, Mirasol Pernia; et al.
Abstract: Aims: Following the peak of the UK COVID-19 epidemic, a new multisystem inflammatory condition with significant cardiovascular effects emerged in young people. We utilized multimodality imaging to provide a detailed sequential description of the cardiac involvement. Methods and Results: Twenty consecutive patients (mean age 10.6 ± 3.8 years) presenting to our institution underwent serial echocardiographic evaluation on admission (median day 5 of illness), the day coinciding with worst cardiac function (median day 7), and the day of discharge (median day 15). We performed cardiac computed tomography (CT) to assess coronary anatomy (median day 15) and cardiac magnetic resonance imaging (CMR) to assess dysfunction (median day 20). On admission, almost all patients displayed abnormal strain and tissue Doppler indices. Three-dimensional (3D) echocardiographic ejection fraction (EF) was <55% in half of the patients. Valvular regurgitation (75%) and small pericardial effusions (10%) were detected. Serial echocardiography demonstrated that the mean 3D EF deteriorated (54.7 ± 8.3% vs. 46.4 ± 8.6%, P = 0.017) before improving at discharge ( P = 0.008). Left main coronary artery (LMCA) dimensions were significantly larger at discharge than at admission ( Z score –0.11 ± 0.87 vs. 0.78 ± 1.23, P = 0.007). CT showed uniform coronary artery dilatation commonly affecting the LMCA (9/12). CMR detected abnormal strain in all patients with global dysfunction (EF <55%) in 35%, myocardial oedema in 50%, and subendocardial infarct in 5% (1/20) patients. Conclusions: Pancarditis with cardiac dysfunction is common and associated with myocardial oedema. Patients require close monitoring due to coronary artery dilatation and the risk of thrombotic myocardial infarction.